Feasibility of Utilizing Recycled Carbon and Polyester Composites for Ship Hull Construction: An Experimental Approach - Muhamad Bilal; Reka Adiyasa Cahyapala; Ashiro Alexander; Adhitya Ramahildan; Parlindungan Manik; Sulardjaka; Wahyu Aditya (International Journal of Marine Engineering Innovation and Research, 2024)
The increasing environmental concerns surrounding fast fashion and the accumulation of waste materials have prompted a need for alternative, sustainable materials in various industries. This study aims to investigate the feasibility of utilizing recycled carbon and polyester composites for ship hull construction. An experimental approach is employed, focusing on tensile testing of material specimens, including carbon fiber and polyester, in accordance with ASTM D3039 standards. The method involves creating composite specimens, subjecting them to tensile tests, and analyzing the results through standard deviation to compare tensile strength and maximum load. The results demonstrate that the composites exhibit suitable mechanical properties for ship hull construction, with polyester showing an insignificant difference compared to carbon fiber composites. These findings provide a reference for future applications in shipbuilding, contributing to environmental sustainability efforts by repurposing waste materials.